Records of the Department of State relating to internal affairs of Bulgaria, 1910-1944 (NARA ;, 1910)
Correspondence, typescript and holograph, of the U.S. State Department concerning internal affairs of Bulgaria, 1910-1944; including newspaper clippings, reports and miscellaneous printed matter.